2022
DOI: 10.3390/cancers14143409
|View full text |Cite
|
Sign up to set email alerts
|

Signature and Prediction of Perigastric Lymph Node Metastasis in Patients with Gastric Cancer and Total Gastrectomy: Is Total Gastrectomy Always Necessary?

Abstract: Background: A growing number of studies suggest that the current indications for partial gastrectomy, including proximal gastrectomy and pylorus-preserving gastrectomy (PPG), may be expanded, but evidence is still lacking. Methods: We retrospectively analyzed 300 patients with gastric cancer (GC) who underwent total gastrectomy. We analyzed the incidence of pLNMs in relation to tumor location, tumor size and T stage. We further identified predictive factors for perigastric lymph node metastasis (pLNM) in stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Yura [20] et al reported a pathological study of 202 patients with T2/T3 proximal gastric cancer who underwent TG showed that The metastatic rates at Nos.4d and Nos.12a were very low (0.99% and 0.006%, respectively), and those at Nos.5 and Nos.6 were zero. Therefore, PG with D1 + lymph node dissection for proximal early gastric cancer is an oncologically safe option [21] . There is no absolute requirement for preservation of the vagus nerve [22] , but when the vagus nerve around the esophagus is cut, it may cause pyloric spasm and dysfunction [14] , and preservation of the hepatic branch of the vagus nerve helps to reduce the occurrence of delayed gastric emptying [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Yura [20] et al reported a pathological study of 202 patients with T2/T3 proximal gastric cancer who underwent TG showed that The metastatic rates at Nos.4d and Nos.12a were very low (0.99% and 0.006%, respectively), and those at Nos.5 and Nos.6 were zero. Therefore, PG with D1 + lymph node dissection for proximal early gastric cancer is an oncologically safe option [21] . There is no absolute requirement for preservation of the vagus nerve [22] , but when the vagus nerve around the esophagus is cut, it may cause pyloric spasm and dysfunction [14] , and preservation of the hepatic branch of the vagus nerve helps to reduce the occurrence of delayed gastric emptying [23] .…”
Section: Discussionmentioning
confidence: 99%